2018
DOI: 10.3390/v10010026
|View full text |Cite
|
Sign up to set email alerts
|

High-Mannose But Not Complex-Type Glycosylation of Tetherin Is Required for Restriction of HIV-1 Release

Abstract: Tetherin is an interferon-inducible antiviral protein that inhibits the release of a broad spectrum of enveloped viruses by retaining virions at the surface of infected cells. While the role of specific tetherin domains in antiviral activity is clearly established, the role of glycosylation in tetherin function is not clear. In this study, we carried out a detailed investigation of this question by using tetherin variants in which one or both sites of N-linked glycosylation were mutated (N65A, N92A, and N65,92… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
4
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 67 publications
0
4
0
Order By: Relevance
“…All these KO cell lines showed increased resistance to PTC3 W14 treatment compared with control cells (Figs 1F-1H and S1D). Furthermore, we also utilized kifunensine, as a potent and selective inhibitor of class I α-mannosidases, to pharmacologically block the synthesis of N-glycans without interfering with cell viability [24,25]. Consistently, pretreatment with kifunensine was also shown to significantly inhibit intoxication by PTC3 W14 (Fig 1I and 1J).…”
Section: Plos Pathogensmentioning
confidence: 58%
“…All these KO cell lines showed increased resistance to PTC3 W14 treatment compared with control cells (Figs 1F-1H and S1D). Furthermore, we also utilized kifunensine, as a potent and selective inhibitor of class I α-mannosidases, to pharmacologically block the synthesis of N-glycans without interfering with cell viability [24,25]. Consistently, pretreatment with kifunensine was also shown to significantly inhibit intoxication by PTC3 W14 (Fig 1I and 1J).…”
Section: Plos Pathogensmentioning
confidence: 58%
“…Thus, depletion of both sites and/or inhibition of N-glycosylation greatly impairs BST2 restriction activity against HIV-1 [172,178] and XMRV [175]. This defect of activity is correlated with a decrease in BST2 expression [172,178] and relocalization of BST2 in subcellular compartments [175]. Together, this suggests that glycosylation of at least one N-glycosylation site of BST2 is required for its efficient transport to the PM where it can trap viruses (Figure 3A).…”
Section: Bst2 Glycosylation Modulates Its Activitymentioning
confidence: 94%
“…Thus, depletion of both sites and/or inhibition of N-glycosylation greatly impairs BST2 restriction activity against HIV-1 [172,178] and XMRV [175]. This defect of activity is correlated with a decrease in BST2 expression [172,178] and relocalization of BST2 in subcellular compartments [175].…”
Section: Bst2 Glycosylation Modulates Its Activitymentioning
confidence: 99%
See 1 more Smart Citation
“…Many previous reports have shown that the release of a broad spectrum of enveloped viruses is significantly blocked in the presence of tetherin also known as bone marrow stromal antigen 2 (Bst-2) [37][38][39]. As such, "physical tethering" by tetherin prevents effective secretion of viral particles and restricts cell-cell transmission of viruses.…”
Section: Determination Of Virus Identitymentioning
confidence: 99%